Digital Da’wah: Content Analysis on the Instagram Platform @pesantrenal_junaidiyah - Asshiddiq, Alwi Ahmad; Akil, Muhammad Anshar (Palakka : Media and Islamic Communication, 2025)
This study aims to analyze the da'wah message on the Instagram account @pesantren_aljunaidiyah, the official media of Pondok Pesantren Modern Al-Junaidiyah Biru, Bone Regency. The research uses a qualitative method with a content analysis approach to understand the themes and forms of da'wah messages uploaded in the form of photos, videos, and narratives of religious activities and pesantren education. Data was collected through literature study from various relevant secondary sources. The results showed that this account consistently presents educational, inspirational, and interactive da'wah content, with a focus on strengthening faith and building the character of students through the values of honesty, noble character, and trustworthiness. The visual approach and light narrative make the da'wah message easily accepted by the younger generation and the wider community. Thus, digital da'wah through this account is effective in expanding the reach of Islamic messages and increasing religious awareness in the era of social media.